2018
DOI: 10.1007/s00705-018-3982-8
|View full text |Cite
|
Sign up to set email alerts
|

A fast and simple one-step duplex PCR assay for canine distemper virus (CDV) and canine coronavirus (CCoV) detection

Abstract: The one-step polymerase chain reaction (one-step PCR) detection assay is an innovative PCR detection method, eliminating nucleic acid extraction steps, in which samples can be directly added to PCR reagents for testing. For simultaneous detection of CDV and CCoV, a sensitive and specific one-step duplex PCR (one-step dPCR) assay was developed with two pairs of primers that were designed based on H and M gene sequences of CDV and CCoV, respectively. The one-step dPCR with optimized detection conditions has high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 22 publications
1
10
0
1
Order By: Relevance
“…All samples were stored at −80 • C to prevent virus deactivation. The infection status and co-infections were assessed by investigating the presence of canine parvovirus 2 (CPV-2), canine distemper virus (CDV), CAdV-1, CAdV-2, canine coronavirus (CRCoV), Canine Circovirus (CACV), and canine bocavirus (CBOV) using polymerase chain reaction (PCR) or real-time PCR, as documented in previous reports (23)(24)(25)(26). The positive infection rate (%) was calculated as follows: Positive infection rate of samples (%) = (number of positive samples/total number of samples) × 100.…”
Section: Clinical Sample Collection and Virus Screeningmentioning
confidence: 99%
See 1 more Smart Citation
“…All samples were stored at −80 • C to prevent virus deactivation. The infection status and co-infections were assessed by investigating the presence of canine parvovirus 2 (CPV-2), canine distemper virus (CDV), CAdV-1, CAdV-2, canine coronavirus (CRCoV), Canine Circovirus (CACV), and canine bocavirus (CBOV) using polymerase chain reaction (PCR) or real-time PCR, as documented in previous reports (23)(24)(25)(26). The positive infection rate (%) was calculated as follows: Positive infection rate of samples (%) = (number of positive samples/total number of samples) × 100.…”
Section: Clinical Sample Collection and Virus Screeningmentioning
confidence: 99%
“…Based on the composition of the fibrillar structural functional regions of human adenoviruses, we found that the structural functional regions of CAdV-2 are composed of amino acids 1-42, 43-365, and 366-542, which are located in the tail, shaft, and head regions, respectively (28)(29)(30). The mutant amino acids in the 19 CAdV-2 strains were located at sites 18,25,26,30,36,37,40, and 41, which were located in the tail of the fibrillar process; sites 44, 45, 50, etc., which were located on the basal axis of the fibrillar process, also known as the shaft; and sites 370, 374, 393, etc., which were located in the ganglion region of Fiber, also known as the knob (Figure 4A). There are four differences between Figures 4B,C at sites 37, 77, 408, 520, 521, 523-532 of Fiber.…”
Section: Protein Structure Predictionmentioning
confidence: 99%
“…At present, detection of CDV infection has mainly relied on RT-PCR or real-time RT-PCR and testing the CDV viral particles using immune colloidal gold test strips. However, RT-PCR assays can only be carried out in well-equipped laboratories (Kim et al 2006;Wang et al 2018), while immune colloidal gold test strip testing is expensive and therefore unsuitable for testing of large numbers of samples. For these reasons, here we developed a sandwich enzyme-linked immunosorbent assay (ELISA) as a sensitive, specific, and easy-to-implement assay for detection of viral antigens that could be suitable for high-throughput testing applications.…”
Section: Introductionmentioning
confidence: 99%
“…Canine distemper is a contagious disease with multisystem infection caused by canine distemper virus (CDV), which affects the health of multiple species (1,2). The disease is characterized by high fever, diarrhea, encephalitis, immunosuppression, and other symptoms.…”
Section: Introductionmentioning
confidence: 99%